2020
DOI: 10.1080/09168451.2019.1676692
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells co-cultured with colorectal cancer cells showed increased invasive and proliferative abilities due to its altered p53/TGF-β1 levels

Abstract: Signaling between cancer cells, their neighboring cells, and mesenchymal stem cells (MSCs) forms the tumor microenvironment. The complex heterogeneity of this microenvironment varies depending on the tumor type and its origins. However, most of the existing cancer-based studies have focused on cancer cells. In this study, we used a direct co-culture system (cross-talk signaling) to induce cross-interaction between cancer cells and mesenchymal stem cells. This induced deformation of MSCs. MSCs showed a diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Due to their direct action on immune cells, MSCs are capable of inhibiting apoptosis or inhibition of T cell proliferation which results in a decline of immunogenic activity [ 16 ]. Furthermore, MSC has also shown pro-metastatic effects that are mediated via paracrine factors, including TGF-β, CXCR4, and CCL5; chemokines secreted from MSC [ 10 , 16 , 17 ]. Martin et al (2010) revealed that the co-culture of bone marrow-derived MSC with breast cancer resulted in the overexpression of EMT-specific genes and a decrease of mesenchymal to epithelial (MET) genes [ 18 ].…”
Section: Mesenchymal Stroma/stem Cells (Msc) and Cancermentioning
confidence: 99%
“…Due to their direct action on immune cells, MSCs are capable of inhibiting apoptosis or inhibition of T cell proliferation which results in a decline of immunogenic activity [ 16 ]. Furthermore, MSC has also shown pro-metastatic effects that are mediated via paracrine factors, including TGF-β, CXCR4, and CCL5; chemokines secreted from MSC [ 10 , 16 , 17 ]. Martin et al (2010) revealed that the co-culture of bone marrow-derived MSC with breast cancer resulted in the overexpression of EMT-specific genes and a decrease of mesenchymal to epithelial (MET) genes [ 18 ].…”
Section: Mesenchymal Stroma/stem Cells (Msc) and Cancermentioning
confidence: 99%
“…Of note, rat BMSCs were found to promote the migration and invasion of CRC (84). Oh et al demonstrated that after co-culturing MSCs with CRC cells, the TGF-b1 and p53 in MSCs increased, which enhanced the invasion and proliferation of CRC (85). hMSCs could differentiate into cancer-associated fibroblasts through CXCR4/TGF-b1 signaling, thereby promoting the growth and metastasis of CRC (86).…”
Section: Roles Of Mesenchymal Stem Cells In Colorectal Cancermentioning
confidence: 99%
“…Long-term culture of human MDA-MB-231 breast cancer cells with normal human MSCs was associated with the formation of three-dimensional (3D) tumor spheroids in vitro , with a 14-fold enhanced expression of the breast tumor marker urokinase plasminogen activator (uPA; Melzer et al, 2019 ). Similarly, MSCs cultured with colorectal cancer cells showed increased invasiveness and proliferative abilities due to increased TGF-β1 and decreased p53 levels ( Oh et al, 2020 ). In another study, TGF-β1 promoted the migration and invasion of HCT116 and HT29 colorectal cancer cells, and induced the differentiation of MSCs into CAFs through a JAK/STAT3 signaling-depended mechanism ( Tan et al, 2019 ).…”
Section: Evidence Of Stromal Cell Programming By Tumor Microenvironmementioning
confidence: 99%